OP24 Subclinical cardiovascular disease and frailty among british older men without a diagnosis of cardiovascular disease: a population-based study. (September 2018) - Patel, M; Papacosta, AO; Lennon, LT; Ellins, EA; Halcox, J; Whincup, PH; Ramsay, SE; Wannamethee, SG
Abstract : Background: Frailty is associated with incident cardiovascular disease (CVD). However, its association with subclinical CVD, which precedes the onset of a CVD event, remains uncertain. Non-invasive vascular markers provide valuable proxy indicators of CVD risk, permitting investigation of risk burden and the development of subclinical CVD. N-terminal pro brain natriuretic peptide (NT-proBNP) and cardiac troponin T (cTNT) are markers of cardiac injury and are strong risk predictors of CVD events such as heart failure and myocardial infarction respectively. Our aim was to examine the association of subclinical cardiovascular markers with frailty in men without a diagnosis of CVD. Methods: In 2010–2012, 1622 surviving men aged 71–92 years were examined and completed a questionnaire as part of a cross-sectional study from a cohort of men from 24 British towns initially recruited in 1978–1980. Using the Fried phenotype, frailty was defined by the presence of ≥3 of the following components: unintentional weight loss, low grip strength, low physical activity, slow walking pace and exhaustion. Carotid intima media thickness (CIMT) and carotid distensibility coefficient (DC) were measured using ultrasound. A Vicorder device was used to measure pulse wave velocity (PWV) and ankle brachial pressure index (ABPI). Fasting blood samples were analysed for NT-proBNP and cTNT. Multivariable logistic regression was used for analyses. Results: Three hundred and three participants (19%) were frail and 876 (54%) were pre-frail. In men without CVD, frail individuals were significantly more likely to be older, physically inactive, have a smoking history and co-morbidities such as peripheral vascular disease and diabetes compared to non-frail individuals (p<0.05 for all associations). Multivariable analyses of baseline demographics and diabetes showed that frailty was positively and significantly associated with high NT-proBNP (odds ratio [OR]=3.48; 95% confidence interval [CI]=2.13–5.67), high cTNT (OR=3.33; 95% CI 2.03 to 5.45) and low DC (reflecting greater arterial stiffness; OR=1.79; 95% CI 1.11 to 2.88). Some subclinical vascular markers (ABPI <0.9 or >1.2, PWV and CIMT) were not associated with frailty (p>0.05). Pre-frailty was also associated with raised cardiac markers (p<0.05 for all associations). Conclusion: Frailty is strongly associated with subclinical CVD markers (NT-proBNP, cTNT and DC), even in the absence of prevalent CVD. Further research is needed to determine whether this association is causal and to understand the underlying mechanisms. Our study findings support the need for screening older individuals with frailty, with the objective of identifying those with an underlying increased risk of CVD and its adverse outcomes.